How Glutamine Expedites Wound Healing - Wong, Aaron Chun Chian; Lee, Enn Enn; Lua, Bee Chen (International Journal of Research in Interdisciplinary Studies, 2025)
Glutamine is one of the amino acids that the body produces. It has various important roles, including muscle repair, rebuilding, protein synthesis, immune function and metabolism. Glutamine supplements are also touted in general for speeding the rate of wound healing. This pertains to the effectiveness of the amino acid to promote tissue repair and modulate immune function. Moreover, Glutamine boosts immunity and reduces inflammation around the wound. This abstract aims to provide a general overview of the existing knowledge regarding the phenomenon of glutamine and its role in wound healing, possibly as a therapeutic agent in the near future. We hereby report the significant improvement of wound healing in a 26-year-old polytrauma patient.